Impact of Uncertainties on the Design and Cost of CCS From a Waste-to-Energy Plant - Roussanaly, Simon; Ouassou, Jabir A.; Anantharaman, Rahul; Haaf, Martin (Frontiers in Energy Research, 2020)
Uncertainties are an inherent and important element of novel systems with limited large-scale industrial experience and must be taken into account in order to enable the design of cost-efficient energy systems. This paper investigates the optimal design of carbon capture and storage from a waste-to-energy plant under uncertainties. With the aim of providing a better understanding of the impact of uncertainties on the design and cost of CCS chains, as well as the capture technology selection, the case of a hypothetical 40 MW waste-to-energy plant located in Norway is considered. The impact of key technical and cost uncertainties on the cost of different CO2 capture and CCS chain options are investigated using an in-house techno-economic CCS assessment tool combined with an uncertainty quantification framework. When the different capture options are compared on a deterministic basis, the advanced amine yields the best performances (CO2 avoidance cost of 153 €/tCO2,avoided), followed by the membrane process based on partial capture (200 €/tCO2,avoided) and MEA-based capture (217 €/tCO2,avoided). However, in contrast with the advanced amine, the partial capture considered in the membrane process does not enable net negative CO2 emissions. Once technical and cost uncertainties are taken into account, the advanced amine-based capture remains the best option, however the MEA-based capture outperform the membrane process. Finally, the stochastic optimisation showed that the uncertainties considered do not impact the optimal capture capacity in this case. The full CCS chain perspective is then included through two chain options: a nearby offshore saline aquifer or an offshore CO2 EOR storage located further away. The EOR-based chain leads to the best performances (187 vs. 202 €/tCO2,avoided) both on a deterministic basis and when different uncertainty scenarios are considered. However, as a shared transport and storage infrastructure is considered, uncertainty regarding the amount of CO2 coming from nearby industries leads to a different optimal design of the chain (pipeline diameter and ship capacity). Finally, uncertainties on the EOR response to CO2 injection can significantly reduce the potential of the CO2 EOR-based chain and lead to cases in which the saline aquifer-based chain would be optimal.